'Wikipedia, the Free Encyclopedia' as a role model? Lessons for open innovation from an exploratory examination of the supposedly democratic-anarchic nature of Wikipedia. (1st January 2010) - Müller-Seitz, Gordon; Reger, Guido
Accounts of open source software (OSS) development projects frequently stress their democratic, sometimes even anarchic nature, in contrast to for-profit organisations. Given this observation, our research evaluates qualitative data from Wikipedia, a free online encyclopaedia whose development mechanism allegedly resembles that of OSS projects. Our research offers contributions to the field of open innovation research with three major findings. First, we shed light on Wikipedia as a phenomenon that has received scant attention from management scholars to date. Second, we show that OSS-related motivational mechanisms partially apply to Wikipedia participants. Third, our exploration of Wikipedia also reveals that its organisational mechanisms are often perceived as bureaucratic by contributors. This finding was unexpected since this type of problem is often associated with for-profit organisations. Such a situation risks attenuating the motivation of contributors and sheds a critical light on the nature of Wikipedia as a role model for open innovation processes.